Clinical and epidemiological profile of the digestive form of Chagas disease in a cohort of patients followed up at the Evandro Chagas National Institute of Infectious Diseases (INI) - Fiocruz - Hasslocher-Moreno, Alejandro Marcel (2022)
Fundação Oswaldo Cruz. Instituto de Pesquisa Clínica Evandro Chagas. Rio de Janeiro, RJ, Brasil.